AGAINST RACIAL DISCRIMINATION IN DENZEL WASHINGTON'S THE GREAT DEBATERS MOVIE (2007): A SOCIOLOGICAL APPROACH - ROCHMANI, PUPUT SARI (2011)
The problem of the study is to reveal how the discrimination between white skin and black skin in United State reflected in Denzel Washington's The Great Debaters. The objectives of the study are to analyze the structural elements of the movie and to analyze the movie based on the sociological perspective. Firstly, based on its structural analysis, Denzel Washington through this movie wants to express his idea about difference rule for black and white skin. He takes the story from the true story about Willey Debate team. Washington is successful in building the plot and portraying the characters through the set-dress, property and cinematography that the elements are well related to one another forming a good unity. Secondly, based on the sociological analysis, the movie is closely related to phenomena which appears in America in 20th century, in which there are many differences in black skin and white skin in getting equality in many social aspects. In America, in that time, black skin is always viewed as second class citizens, never gets something the same as white skin. Based on this movie, Washington wants to show that black and white skin basically is the same except the color of the skin. In this movie he tells many aspects of live unfair get by black skin because of their skin, economic aspect, social aspect. Through this movie, Washington opens new point of view that black skin also can defeat white skin by debate and win. He wants to tell that there is no difference among people.